1996
DOI: 10.1002/srin.199605504
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of structural stability and creep resistance of 9-12% Cr steels

Abstract: During creep exposure of modified chromium steels lowering of solid solution strengthening due to precipitation of Laves phase as well as coarsening of all precipitates causes degradation of creep resistance. Two distinct domains of the stress dependence of creep rate and time to rupture have been observed in precipitation strengthened modified chromium steels. The stress characterizing the transition between these domains was found to be closely related to the Orowan stress. This stress consists in these stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…In order to simulate the evolution sequence of carbides, some specimens of the same material were prepared, but they were first quenched in oil at a temperature of 1040 • C. This temperature ensured the solution of all carbide particles in austenite. [3] Specimens of steel were then tempered from 1 to 1344 h at 800 • C.…”
Section: Methodsmentioning
confidence: 99%
“…In order to simulate the evolution sequence of carbides, some specimens of the same material were prepared, but they were first quenched in oil at a temperature of 1040 • C. This temperature ensured the solution of all carbide particles in austenite. [3] Specimens of steel were then tempered from 1 to 1344 h at 800 • C.…”
Section: Methodsmentioning
confidence: 99%
“…Other authors [11] have shown that the size of the Laves phase is of great significance to the creep properties. On the basis of short-term creep tests, other investigations concluded that Laves phase particles grow and coarsen very rapidly [12,13].…”
Section: Introductionmentioning
confidence: 97%
“…The VN-precipitates are highly resistant to coarsening at 600 and 650°C, contributing to long-term creep strength of the material [4,10]. The Laves phase particles may strengthen the steel, but the solid solution strengthening of the matrix is decreased, especially after coarsening of Fe 2 (W,Mo) [6,[11][12][13]. Dislocation density decreases and the sub-grain width increases by factor of 3-5 during aging at stress applied [4].…”
Section: Introductionmentioning
confidence: 99%